Comparative Thermal Analysis of Different Cool Roof Materials for Minimizing Building Energy Consumption. (17th December 2014) - Anand, Y.; Gupta, A.; Maini, A.; Gupta, Avi; Sharma, A.; Khajuria, A.; Gupta, S.; Sharma, S.; Anand, S.; Tyagi, S. K.
Abstract : The roof and walls in the urban areas contribute to major share in the absorption of solar radiations and also retard the outflow of the absorbed radiation from the building envelope, thereby increasing the global warming by inducing the heat island effect. The impact of using cool roof technologies on the thermal comfort of the office buildings has been estimated. Cool roofs reduce electricity consumption for maintaining the temperature of the air-conditioned buildings in the comfort level and also increase comfort in buildings merely not relying completely on cooling equipment. The cool roofs and cool pavements, however, can mitigate summer urban heat islands by improving indoor air quality and comfort. The thermal analysis of different materials has been carried out to analyze the impact of the rate of heat transfer on the building envelope and the results obtained indicate that different cool roof techniques are beneficial in maintaining the comfort level of the building which purely depends on the ambient temperature conditions.